Investigation of the double-lobed sources of the Cygnus constellation core. (7th September 2021) - Saponara, J.; Benaglia, P.; Andruchow, I.; Ishwara-Chandra, C. H.; Intema, H. T.
Abstract: We present a collection of double-lobed sources towards a $20\, deg^2$ area of the Cygnus region at the northern sky, observed at 325 and 610 MHz with the Giant Metrewave Radio Telescope. The 10 $^{′′}$ resolution achieved at 325 MHz is 5.5 times better than previous studies, while at 610 MHz, these are the first results ever of such a large area, mapped with 6 $^{′′}$ angular resolution. After a thorough visual inspection of the images at the two bands, we found 43 double-lobed source candidates, proposed as such due to the presence of 2 bright peaks, within a few arcminutes apart, joined by a bridge or a central nucleus. All but two are presented here as a double-lobed candidates for the first time. Thirty nine of the candidates were covered at both bands, and we provide the spectral index information for them. We have searched for positional coincidences between the detected sources/components and other objects from the literature, along the electromagnetic spectrum. Twenty-three candidates possess radio counterpart(s), 12 present infrared counterparts, and 1 showed an overlapping X-ray source. We analysed each candidate considering morphology, counterparts, and spectral indices. Out of the 43 candidates, 37 show characteristics compatible with an extragalactic nature, 2 of probably Galactic origin, 3 remain as dubious cases, though with feature(s) compatible with an extragalactic nature, and the remaining one, evidence of physically unrelated components. The median spectral index of the 40 putative extragalactic sources is $-1.0$ . Their celestial surface density at 610 MHz resulted in $1.9\, \mathrm{per\ deg}^2$, across a region lying at the Galactic plane.